The invisible link : - Yoshino, M., Y. (MIT Press, 1986)
The Invisible Link gives detailed coverage to such topics as historical evolution of the sogo shosha, strategic responses and competitive dynamics, culture and organization, administrative structures and processes, human resource systems, career outcomes, interunit and interfirm coordination, sectional and network organization, and emerging challenges as the nature of the Japanese economy changes.